2009
DOI: 10.14429/dsj.59.1575
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic Characteristics of Drop-substrate Interactions in Direct Ceramic Ink-jet Printing using High Speed Imaging System

Abstract: (DCIJP). The DCIJP finds applications in the fabrication of complex-shaped monolithic ceramic parts, ceramic composites, solid-oxide fuel cells, integrated circuits, components of fuel cells, gas turbines, ceramic tiles used in space vehicles, and many other equipments operating at high temperature owing to their ability to retain strength at high temperature. Ceramic pottery industry can also benefit from this process.The DCIJP uses ceramic powder presented in a carrier medium which is deposited using a deliv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 8 publications
(10 reference statements)
0
2
0
Order By: Relevance
“…The splash phenomenon has been studied in many different contexts, including ink‐jet printing (Somasundaram et al, ), fuel spray injection (Andreassi et al, ), aerosol generation (Joung & Buie, ), transfer of infectious bacteria (Boyer, ), and soil erosion (Jomaa et al, ; Morgan, ). These studies can be divided into two main groups: (i) rupturing of a drop into many droplets as a result of its impact on a solid surface (Josserand & Thoroddsen, ; Lan et al, ; Liu et al, ; Mandre et al, ) and (ii) simultaneous rupturing of a drop and ejecting of granules as a result of the drop's impact on a granular bed (Marston et al, ; Van der Meer, ).…”
Section: Introductionmentioning
confidence: 99%
“…The splash phenomenon has been studied in many different contexts, including ink‐jet printing (Somasundaram et al, ), fuel spray injection (Andreassi et al, ), aerosol generation (Joung & Buie, ), transfer of infectious bacteria (Boyer, ), and soil erosion (Jomaa et al, ; Morgan, ). These studies can be divided into two main groups: (i) rupturing of a drop into many droplets as a result of its impact on a solid surface (Josserand & Thoroddsen, ; Lan et al, ; Liu et al, ; Mandre et al, ) and (ii) simultaneous rupturing of a drop and ejecting of granules as a result of the drop's impact on a granular bed (Marston et al, ; Van der Meer, ).…”
Section: Introductionmentioning
confidence: 99%
“…The following factors will influence the wetting behavior: the intrinsic properties of the ink, the chemical contents, and physical structure of the substrates. Many researches concerning the interactions between water and porous substrates have been conducted to control the wetting behavior. For instance, Kalakkath et al showed that the penetration of a ceramic ink on a porous ceramic substrate (Al 2 O 3 /SiC) decreased as ink viscosity increased. The investigation showed that nozzle geometry, applied pressure, solution viscosity, and surface tension of a ceramic ink can affect satellite drop formation as well as the resolution.…”
Section: Introductionmentioning
confidence: 99%